Supply-side determinants of cataract surgery output in South Africa - Marais, Charl (Division of General Surgery, 2026)
Background Globally, cataracts represent the leading cause of blindness1. Although South Africa meets the Vision 2020: Right to Sight target of ophthalmologists per million population2, it has not met the target of performing 2,000 cataract surgeries per million population to address avoidable cataract blindness3-5. Aim: To explore the supply-side determinants of cataract surgery output by examining provider characteristics and perceived barriers, enablers, and strategies to increase surgical volume. Methods: A cross-sectional study, using an emailed online questionnaire, was performed using convenience sampling on 399 medically trained members of the Ophthalmology Society of South Africa (OSSA) between May and June 2024. Results: The study's response rate was 19.7% (79/399). In 2023, nearly half of the surgeons performed fewer than 200 cataract surgeries, while only 15% performed 500 or more. Factors associated with performing ≥201 cataract surgeries were: male gender, experience, working in the private sector, performing phacoemulsification cataract surgery and spending less time on non-surgical responsibilities.(p <0.05). The most frequently reported barriers to increasing surgical output were non-surgical responsibilities (28%), limited theatre time (25%), patient access issues (24%), and inconsistent consumable supplies (22%), especially in the public sector. Having adequate theatre staff (56%), dedicated eye theatres (49%), equipment (43%), and motivated staff (41%) were the main enablers identified. Participants recommended strategies such as increasing theatre utilisation (24%), ensuring a stable supply of consumables (24%) and improving staff motivation (19%) to increase cataract surgery in South Africa. Conclusions: Cataract surgery output in South Africa is inadequate. Addressing reported provider barriers, promoting enablers and implementation strategies identified will likely improve surgeon utilisation and increase cataract surgery output rates in the country. Contribution: Provider's cataract surgery output and views of barriers, enablers and implementation strategies to improve cataract surgery output in South Africa.